Pengembangan Media Video Berbasis pendekatan Saintifik Berbantuan Canva Pada Materi Sistem Pencernaan Kelas V SD Negeri 1 Sambijajar - Dea Wulandari; Rohmatus Syafi’ah; Eka Yuliana Sari (Journal on Education, 2024)
Research on the development of video media based on a scientific approach assisted by Canva was motivated by learning that focused on Student Worksheets (LKS) and there was no media on the digestive system material. This research aims to develop and describe the validation of learning media results in the form of videos. This research uses the Analysis, Design, Development, Implementation, Evaluation (ADDIE) development model. This research instrument uses a questionnaire. The validity of the video is seen from the validation results by each of the two validators (media, material, language experts), users (student responses), practitioners (teacher responses). The validation results of video learning media on the digestive system material from media experts received an average score of 90% in the "very valid" category. The material expert assessment received a score of 90%. The linguist's assessment received an average score of 90% in the "very valid" category. The product validation results from teachers got 90% and tests on 22 class V users (students) got 88% in the "very valid" category. So it can be concluded that videos based on scientific approaches assisted by Canva are "very valid" and can be used in the learning process.